Comparing the Effects of Patient-Centered and Family-Centered Empowerment Model-Based Training on Perceived Self-Efficacy and Fasting Blood Glucose in Patients with Type 2 Diabetes - Seyyed Kamaladdin Mirkarimi; Abdolhalim Rajabi; Ali Maghsoudloo (مجله دانشگاه علوم پزشکی گرگان)
Background and Objective: Family-centered empowerment involves engaging clients and their families in decision-making processes to improve health outcomes, thereby enabling them to exert control over their health status through informed choices. Self-efficacy is considered the most crucial component of empowerment and holds significant importance in the management of chronic diseases and the enhancement of self-efficacy. This study was conducted to compare the effects of patient-centered and family-centered empowerment model-based training on perceived self-efficacy and fasting blood glucose levels in patients with type 2 diabetes mellitus. Methods: This quasi-experimental study was conducted on 120 patients with type 2 diabetes who attended rural comprehensive health centers in Gorgan, Iran, during 2023. Patients were enrolled in the study using a multi-stage cluster sampling method and were divided into three groups of 40: A control group, a family-centered empowerment group, and a patient-centered empowerment group. The interventions in the patient-centered and family-centered groups were delivered in 6-8 people groups based on a four-stage model. These stages included threat perception, problem-solving, educational participation, and evaluation. Patients in the control group received only the routine health center training. Data collection instruments included the standard Perceived Self-Efficacy Questionnaire in middle-aged diabetic patients and a checklist for recording clinical characteristics. Results: The fasting blood glucose levels decreased in all three groups after the intervention; however, this difference was not statistically significant among the groups in either the pre-test or the post-test. In the post-test, a statistically significant increase in perceived self-efficacy was observed between the patient-centered group and the family-centered group, as well as between the patient-centered group and the control group (P<0.05). Conclusion: The patient-centered and family-centered empowerment model-based training on patients’ perceived self-efficacy was evaluated as effective; however, it had no effect on the fasting blood glucose levels of patients with type 2 diabetes.